Generation mechanism and remedy method of rail corrugation at a sharp curved metro track with Vanguard fasteners. Issue 2 (June 2020) - Wu, BW; Chen, GX; Lv, JZ; Zhu, Q; Kang, X
In Chinese metro lines, Vanguard fastener system is widely used as vibration damping fastener. However, the rails mounted with this fastener system are deeply affected by rail corrugation. The generation mechanism of corrugation wear at a metro track mounted with Vanguard fastening is revealed through the numerical simulation method. A finite element model including two rails, the track system, and a leading wheelset is set up. The parameter sensitivity analysis is conducted to identify the dominant factors affecting the rail corrugation. Then, the remedy method to suppress the corrugation wear is put forward on the basis of the parameter analysis results. The results indicate that the severe corrugation wear on the inner rail is attributed to the self-sustained vibration of the wheelset–track system aroused by the saturated wheel–rail creep force. The frequency of the rail corrugation calculated by the model is very close to the measured data. The elastic modulus and the damping coefficient of the rubber rest pad in the Vanguard fasteners have a high impact on rail corrugation. Increasing the elastic modulus and the damping coefficient can effectively restrain or even eliminate the rail corrugation. Bringing the damping coefficient of the rubber rest pad above 0.0001 can significantly alleviate the rail corrugation. The influence of the damping and stiffness of the rubber pad under the floating slab track bed is negligible.